2019
DOI: 10.1080/00103624.2019.1648498
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Yield, Nitrogen Accumulation and Nutritive Value of Mavuno Grass Inoculated with Plant Growth-promoting Bacteria

Abstract: The objective of this study was to evaluate the effects of strains of Azospirillum brasilense, Pseudomonas fluorescens and Rhizobium tropici on the shoot dry weight (SDW) and root dry weight (RDW) yield, N uptake and nutritive value of 'Mavuno' grass inoculated with plant growth-promoting bacteria. We evaluated the effects of inoculation with the Ab-V5 and Ab-V6 strains of Azospirillum brasilense and Pseudomonas fluorescens or coinoculation with Rhizobium tropici and Ab-V6, with and without nitrogen (N) applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The similar P content in the different treatments, with the exception of the combination treatment that decreased it, and the lowest N content in Az39 and Rt6M10 (similar to the control) could be related to the use of a soil with adequate levels of nutrients (Sá et al 2019) and to the fact that the samples were collected in the reproductive stage when the plant allocates nutrients to form the fruits.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The similar P content in the different treatments, with the exception of the combination treatment that decreased it, and the lowest N content in Az39 and Rt6M10 (similar to the control) could be related to the use of a soil with adequate levels of nutrients (Sá et al 2019) and to the fact that the samples were collected in the reproductive stage when the plant allocates nutrients to form the fruits.…”
Section: Discussionmentioning
confidence: 89%
“…The different letters indicate significant differences using Fisher's LSD test at P < 0.05 a Expressed as citric acid equivalent be different than the effect produced by each bacterium alone. However, other authors reported positive effects by using different consortiums in maize (Couillerot et al 2013), cucumber (Wang et al 2012), forage plants Mavuno grass (Sá et al 2019), and forest species Nothofagus alpina (Martínez et al 2018). These contradictory results with the use of combinations may be related to the correct concentration of each inoculum.…”
Section: Discussionmentioning
confidence: 95%
“…In general, nutrient accumulation in the shoots and roots of Zuri Guinea grass was positively affected by inoculation with PGPB. The nutrient with the greatest accumulation were N, important nutrients for forages [66]; [67]. The increases in N accumulation, benefited mainly by the inoculation with the Azospirillum and Pseudomonas, might be attributed mainly to the synthesis of phytohormones, improving root biomass and, in the case of Azospirillum, probably also by a contribution of biological nitrogen fixation [21]; [68].…”
Section: Shoot Dry Weight Yields and Numbers Tillers And Relative Chlmentioning
confidence: 99%
“…The treatment inoculated with A. brasilense Ab-V5 + Ab-V6 accumulated 37% more, differing statistically from the positive control. The total N concentration and total N accumulation in the shoots of Zuri Guinea grass showed positive effects when the plants were inoculated with PGPB, probably explained by the increase in root volume and consequently greater absorption of water and nutrients [67]; [66]. The benefits were mainly attributed to the strains of Azospirillum and Pseudomonas.…”
Section: Total N Concentration and Total N Uptake In Shootsmentioning
confidence: 99%
“…The inoculation of forage grass seeds with plant growth-promoting bacteria (PGPB) has shown positive results in recent studies [6]; [7]; [8], this technique could reduce nitrogen fertilization costs in tropical pastures [9]; [10].…”
Section: Introductionmentioning
confidence: 99%